2017
DOI: 10.1007/978-3-662-54434-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Confluence of Graph Rewriting with Interfaces

Abstract: Abstract. For terminating double-pushout (DPO) graph rewriting systems confluence is, in general, undecidable. We show that confluence is decidable for an extension of DPO rewriting to graphs with interfaces. This variant is important due to it being closely related to rewriting of string diagrams. We show that our result extends, under mild conditions, to decidability of confluence for terminating rewriting systems of string diagrams in symmetric monoidal categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In [8], it is proven that confluence is decidable for terminating rewrite systems on graphs with an interface, which embed those considered in the present paper (as mentioned above, confluence is undecidable in general in graph rewriting). In our results, the rewrite rules we consider are not necessarily terminating (and equations are not even orientable in general).…”
Section: Related Worksupporting
confidence: 60%
“…In [8], it is proven that confluence is decidable for terminating rewrite systems on graphs with an interface, which embed those considered in the present paper (as mentioned above, confluence is undecidable in general in graph rewriting). In our results, the rewrite rules we consider are not necessarily terminating (and equations are not even orientable in general).…”
Section: Related Worksupporting
confidence: 60%
“…Moreover, he also proved that (local) confluence of graph transformation systems is undecidable, even for terminating systems, as opposed to what happens in the area of term rewriting systems. However, recently, in [2] it is shown that confluence of terminating DPO transformation of graphs with interfaces is decidable. The authors explain that the reason is that interfaces play the same role as variables in term rewriting systems, where confluence is undecidable for terminating ground (i.e., without variables) systems, but decidable for non-ground ones.…”
Section: Related Workmentioning
confidence: 99%
“…One of the most popular graph rewriting approaches is known as double pushout (DPO) rewriting [9], and we shall now recall some of its basic notions in relation to linear hypergraphs. We use an extension of the traditional definition that introduces an 'interface' [4]. Intuitively, the pushout complement is G with L removed.…”
Section: Graph Rewritingmentioning
confidence: 99%